A study of information needs and uses of agricultural scientists working in research institutes within the Agency for Agricultural Research and Development (AARD) in Indonesia - Wiryoadipoero, Soewarto (Institute of Library Science, University of the Philippines Diliman, 1984)
The aim of this study is to identify the information needs and uses of agricultural scientists working in research institutes within the Agency for Agricultural Research and Development (AARD) in Indonesia, in relation with information services being provided by the National Library for Agricultural Sciences (NLAS) in support of their research activities. It was designed and carried out in November and December 1983.A comprehensive questionnaire was developed and distributed to 300 agricultural scientists 214 or 71 percent of whom responded.